Prevalence of Methicillin Resistant Staphylococcus aureus and Antibiotic Susceptibility Pattern in a Tertiary Hospital in Nepal - Khanal, Laxmi Kant; Adhikari, Ram Prasad; Guragain, Ankita (Journal of Nepal Health Research Council, 2018)
Background: Methicillin resistant Staphylococcus aureus is a global health challenge nowadays creating problem in antibiotic therapy. This study was aimed to generate resistance pattern of Methicillin resistant Staphylococcus aureus to various antibiotics in order to formulate antibiotic policy for control of Methicillin resistant Staphylococcus aureus in Nepal. Methods: This was a cross-sectional study conducted at the department of Clinical Microbiology, Nepal Medical College Teaching Hospital, from April 2015 to March 2016. A total of 142 S. aureus isolated from various clinical specimens. were screened for Methicillin resistant Staphylococcus aureus by cefoxitin disc method according to Clinical and Laboratory Standards Institute guidelines. Results: Out of 142 S. aureus isolates, 30 (21.1%) were detected as Methicillin resistant Staphylococcus aureus by cefoxitin disc method. Most of the Methicillin resistant Staphylococcus aureus (25/30) were isolated from pus which were collected from OPD patients. Antibiotic sensitivity pattern showed all Methicillin resistant Staphylococcus aureus isolates were sensitive to vancomycin. Conclusions: Prevalence of Methicillin resistant Staphylococcus aureus was found to be 21.1%, and all Methicillin resistant Staphylococcus aureus appear 100% sensitive to vancomycin. Keywords: .